2006
DOI: 10.1016/s0828-282x(06)70990-4
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness or endothelial dysfunction as a surrogate marker of vascular risk

Abstract: T he understanding of the pathophysiology of atherosclerosis and its vascular complications has increased dramatically over the past decade. Numerous measurable biomarkers play a role in the atherosclerosis process, and are associated with clinically important vascular events. Not only has their evaluation advanced our knowledge of the atherosclerotic process but it has also accelerated a search for new diagnostic tools to aid in risk stratification. Putative factors include soluble biomarkers and imaging asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 129 publications
1
115
1
4
Order By: Relevance
“…18,19 Cardiovascular effects of coffee consumption and notably the development of AS can be mediated also through insulin-resistance mechanisms. 20 AI, a hallmark of vascular aging, is assessed also by the renal resistive index (RRI), and a relationship between the ultrasound RRI, BP, and renal function response is recognized as a most powerful predictor of death during follow-up of patients with atherosclerotic renovascular disease. 21 However, increased RRI may imply the presence of some type of underlying renal damage, including ischemic nephropathy, 22 and is useful for predicting long-term renal functions in renal transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Cardiovascular effects of coffee consumption and notably the development of AS can be mediated also through insulin-resistance mechanisms. 20 AI, a hallmark of vascular aging, is assessed also by the renal resistive index (RRI), and a relationship between the ultrasound RRI, BP, and renal function response is recognized as a most powerful predictor of death during follow-up of patients with atherosclerotic renovascular disease. 21 However, increased RRI may imply the presence of some type of underlying renal damage, including ischemic nephropathy, 22 and is useful for predicting long-term renal functions in renal transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has shown that HC leads to AS by causing ED, which is a marker of cardiovascular (Anderson, 2006) and atherosclerotic (Bonetti et al, 2003) risk and responsible for the triggering of the first step of AS (Ross, 1993). Consistent with the idea that the TC and LDL are the major harmful factors for endothelial function, and the higher levels of TC/LDL, the greater the arterial stiffness (Diehm et al, 2004), we found that FMD, β, and IMT were still correlated significantly with TC after adjustment for the other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave velocity is a surrogate marker of arterial stiffness that has been associated with CVD and [21]. There is limited data on PWV in HIV-infected women, and only two studies reported on gender in their results.…”
Section: Pulse Wave Velocity (Pwv)mentioning
confidence: 99%